Screening of the TMEM151A Gene in Patients With Paroxysmal Kinesigenic Dyskinesia and Other Movement Disorders - Ma, Ling-Yan; Han, Lin; Niu, Meng; Chen, Lu; Yu, Ya-Zhen; Feng, Tao (Frontiers in Neurology, 2022)
Background Paroxysmal kinesigenic dyskinesia (PKD) is a rare neurological disorder characterized by recurrent involuntary movements usually triggered by sudden movements. Mutations in the TMEM151A gene were found to be the causative factor of PKD in recent studies. It has also been revealed that loss-of-function is the mechanism by which TMEM151A mutations cause PKD. Methods To investigate the genetic basis of PKD and broaden the clinical spectrum of the TMEM151A mutations, we recruited 181 patients of Chinese origin with movement disorders (MDs), including 39 PRRT2-negative PKD, 3 paroxysmal exercise-induced dyskinesia (PED), 2 paroxysmal non-kinesigenic dyskinesia (PNKD), 127 isolated dystonia, 8 choreas, and 2 myoclonus-dystonia syndromes. Whole-exome sequencing was applied to identify their possible disease-causing mutations. Then, Sanger sequencing was performed for validation and co-segregation analysis. Genetic analysis was also performed on additional family members of patients with TMEM151A mutations. Clinical manifestations of all PKD cases with mutations in TMEM151A reported, so far, were reviewed. Results Two novel variants of the TMEM151A gene (NM_153266.4, NP_694998.1), c.627_643dup (p.A215Gfs*53) and c.627delG (p.L210Wfs*52), were identified in 2 patients with PKD by whole-exome sequencing and further Sanger sequencing. Both variants were inherited by the patients from their respective mothers. No mutation of the TMEM151A gene was found in the other type of movement disorders. In reviewing the clinical presentation of TMEM151A-related PKD, no statistically significant difference in the age of onset, family history, duration of attacks, laterality, and phenotype was found between genders. More male patients received treatment and had a good response. A higher proportion of female patients did not receive any treatment, possibly because they had a milder condition of the disease. Conclusions This study further validated the role of TMEM151A in PKD. Future studies on protein function will be needed to ascertain the pathogenesis of TMEM151A in PKD.